Muslim Centred user interface design prototype / Zan Azma Nasruddin and Husnayati Hussin - Nasruddin, Zan Azma; Hussin, Husnayati (Research Innovation Business Unit, 2014)
There are challenges and dilemmas in recognizing values and ideals in culture on interface design. Every culture shares different experiences and values (Lakoff, G., Johnson, 1980). As value added in interface design related to the culture, the element of culture values should play an important role so that users are encouraged to feel the beauty of them in computer interface. Currently, majority of the designs are from USA, their interfaces have therefore been primarily based on American metaphors, representations, and associations logics. The standardization of information technology has the advantage of compatibility. Marcus recommends that designers “would do well to consider their own cultural orientation and to understand the preferred structures and process of other cultures” (Marcus & Gould, 2000). While some works have been reported on the development of metaphors and icons design based on Chinese culture (Shen, 2006) and African culture (Heukelman, 2006), none have been explored for desktop interface design for Islamic culture. Good Islamic values should be practiced all the time even in computer usage. Considering Muslims are among the computer users in everyday life, it comes as a big responsibility as a designer to insert values on interface design as to educate and as a reminder to the users. Thus, the development of the interface prototype called Muslim Centered User Interface Design (MCUID) is created based on the Culture Centered Design (CCD) framework. The framework is an adaptation of Shen et. al (2006) work on cultural filter. There are two types of filters in the framework. The first filter dedicated for a designer. The designer comes from cultural origin, and then he identifies a target group, which are among Muslim users. Next, the designer understands the target user’s cultural data which is focusing on Islamic culture. Later, the designer creates visual images for the interface design based on personal experience and observation in particular socio-cultural background, knowledge from literature review including Quran and hadith. Other factors that shape up designer’s view include technology, usability and mental models. The second filter is dedicated to user, Whenever the mental model between designer and user are matched, the product (interface design) is considered successful. In developing technology, the question of the responsibilities of the designer as the ones with technological knowledge and expertise is very significant. Islam emphasis that all men should be responsible for their own doing. Designers should use their knowledge conscientiously for the good community. Through the interface prototype design called MCUID, the image of the mosque is used as background to represent an Islamic identity. Besides, metaphor icons are created to represent analogies in Islamic values. MCUID is hoped to educate or as reminder to computer user because MCUID enriched with values in Islamic culture. Therefore, possibly, technology could be shaped by Muslims designers by giving more meaningful user experience towards the interface design. The evaluation on MCUID was done among students from UiTM and students from Darul Quran. There were several patterns of findings were discovered. The findings were analysed using Atlas.ti 7.